Atenção conjunta digital entre crianças em aquisição da linguagem e um livro interativo digital. - Barros, Flavio Romulo Alexandre do Rego (2024)
Joint attention, also known as shared attention, refers to individuals' ability to direct their attention to a common object, event, or task, involving social interaction. It is an important concept in child development, social psychology, and the study of linguistics. We believe that joint attention can be present in a digital book, providing a new specificity of Joint Attention. The production of gestural movements by the child in response to interaction with the multimodal imagery resources present in the book can reveal this process of child engagement in the digital environment. This thesis aims to investigate the process of Digital Joint Attention (DJA) among children in language acquisition and a digital book through the mediation of a virtual narrator. Our research is guided by studies on Joint Attention by Bruner (1983), Tomasello (2003, 2019); on the concept of Virtual Joint Attention, established by Costa Filho (2011; 2016; 2017; 2018; 2021); on the multimodal perspective, discussed in Kendon (1988; 2009), McNeill (1985; 1992; 2000, 2005, 2012, 2016), Cavalcante (1999; 2018, 2009), Fonte (2011), Fonte et al (2014), Melo (2015); Nóbrega (2017) and on the enunciative studies of Benveniste (2005; 2006). In our research, epistemological perspectives and qualitative approaches were adopted. However, it is important to note that the observed and described data were also subjected to quantification processes. In the qualitative approach, we highlight the linguistic productions resulting from the process of Digital Joint Attention (DJA) between children and the digital book, paying attention to singularities and individual experiences. In the scope of quantitative analysis, we approached the phenomena through the collection of numerical data. Specifically, we investigated which types of Joint Attention were most evidenced and recurrent in the interaction with the digital book, providing insights into preferences, behaviors, and other actions of individuals. Data collection was carried out through recordings of children's interaction with digital books. The corpora were recorded in audiovisual materials, considering a group of 3 children aged between 6 and 8 years old. We used as inclusion criteria all children having typical development and being enrolled in a regular school. The research developed in the thesis confirmed that the multimodal imagery resources present in the book, together with the gestural movements produced by the children during reading, were able to demonstrate their engagement in scenes of Digital Joint Attention. This perspective opens the possibility for digital book production to consider these resources, promoting digital joint attention. These resources can be incorporated into supplementary or educational books, enabling a more effective understanding by children of the narratives present in these books. This, in turn, would facilitate the language acquisition process, with the support of the digital environment, and potentially contribute to learning in general.